2015
DOI: 10.1111/trf.13345
|View full text |Cite
|
Sign up to set email alerts
|

Extended storage and glucose exhaustion are associated with apoptotic changes in platelets stored in additive solution

Abstract: Exhaustion of glucose was associated with a proapoptotic phenotype. Results such as these should be considered before extending the PLT shelf life beyond 7 days, particularly when stored in ASs lacking glucose with low plasma carryover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
3
18
1
Order By: Relevance
“…As anticipated, cold‐storage was sufficient to prevent the accelerated glycolytic metabolism associated with UVC‐treatment. The availability of an adequate supply of energy during ex vivo storage has a substantial impact on platelets, with depletion of glucose being linked with decreased viability . Thus, the reduction in glycolytic metabolism afforded by cold storage provided UVC‐treated platelets with sufficient glucose for at least an extra two days of storage, compared to RT‐UVC platelets which had exhausted their glucose reserves by day 7.…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated, cold‐storage was sufficient to prevent the accelerated glycolytic metabolism associated with UVC‐treatment. The availability of an adequate supply of energy during ex vivo storage has a substantial impact on platelets, with depletion of glucose being linked with decreased viability . Thus, the reduction in glycolytic metabolism afforded by cold storage provided UVC‐treated platelets with sufficient glucose for at least an extra two days of storage, compared to RT‐UVC platelets which had exhausted their glucose reserves by day 7.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the clinical impact is unknown, this automated method did not have an influence on the level of RANTES and sCD40L, and BRS‐A had little or no influence on the accumulation of PDMP, RANTES, and sCD40L in storage media during 3 days of storage. Johnson et al demonstrated that PLT apoptosis (annexin V binding) was initiated for extended storage periods, which was likely linked to exhaustion of glucose in storage media. Like this report, the present study showed that annexin V binding increased largely and aggregation response and HSR deteriorated on Day 7, along with depletion of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of platelet concentrates increases with storage [10, 13, 32, 33] and with pathogen-reduction processing [5, 13] and varies greatly between normal donors [13, 3436]. The largest contributor to platelet heterogeneity is the microparticle content (Figure 1(b)).…”
Section: Platelet Quality From the Perspective Of Productionmentioning
confidence: 99%
“…Because the emphasis is to detect degradation from the beginning to the end of the current 5-day shelf life [5, 6], the resolution of current quality measures has been tuned to be high for small changes on the “resting/viable” end of the quality spectrum but becomes low on the “activated/functional” end of the quality spectrum. Additional changes are seen upon extended shelf life which become more important as bacterially tested or pathogen inactivated platelets may be stored for 7 days.…”
Section: Introductionmentioning
confidence: 99%